2014
DOI: 10.1111/1556-4029.12447
|View full text |Cite
|
Sign up to set email alerts
|

A Time Course Study Demonstrating mRNA, microRNA, 18S rRNA, and U6 snRNA Changes to Estimate PMI in Deceased Rat's Spleen

Abstract: Determining the postmortem interval (PMI) is important in criminal, civil, and forensic cases. We examined the feasibility of using the transcript abundances of mRNAs, 18S rRNA, U6 snRNA, and microRNAs as a means to estimate the PMI. We removed spleen tissues from rats at different PMIs under 4°C or 25°C and examined gene transcript abundances in these samples by RT-qPCR. Using the algorithm geNorm, we found that microRNAs to be appropriate control markers because they were less affected by PMI and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 29 publications
0
48
1
Order By: Relevance
“…To overcome this, we focused primarily on miRNA, which maintains stable signal even in degraded human tissue RNA preparations32 and has been shown to undergo few signs of degradation in the first 24 hours post-mortem73334. Although we applied a cautious approach to our mRNA analysis, using it as a secondary validation of our miRNA findings, it is nevertheless worth noting that we found minimal differences between groups in terms of RNA purity or levels of endogenous (SNORD44) mRNA with RNA yield actually being higher in cadaveric samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this, we focused primarily on miRNA, which maintains stable signal even in degraded human tissue RNA preparations32 and has been shown to undergo few signs of degradation in the first 24 hours post-mortem73334. Although we applied a cautious approach to our mRNA analysis, using it as a secondary validation of our miRNA findings, it is nevertheless worth noting that we found minimal differences between groups in terms of RNA purity or levels of endogenous (SNORD44) mRNA with RNA yield actually being higher in cadaveric samples.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-ribonucleic acids (microRNAs/miRNAs) are small, non-coding RNAs that act to inhibit translation of messenger RNA (mRNA) into proteins and are involved in many cardiovascular diseases6. MiRNAs have been well reported as being stable in post-mortem tissue under a variety of conditions, most likely due to their small size and binding to proteins such as Argonaute-278. Previous studies involving miRNAs in CAVD have used microarrays to compare stenotic to regurgitant bicuspid valves9, tricuspid to bicuspid valves10, and endothelial cells in varying flow conditions11, as well as manipulation of a single miRNA, miR-30b, in aortic valvular interstitial cells12.…”
mentioning
confidence: 99%
“…GAPDH is one of the housekeeping genes that had shown time dependent quantitative changes with PMI in previous studies (Inoue et al 2002;Sampaio-Silva et al 2013 andLv et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we only used one mRNA marker. We preferred to focus on a specific skin marker to detect its degradation pattern as recommended by Lv et al (2014), who demonstrated that each RNA had a specific degradation pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bergboer et al (2011) andSampaio-Silva et al (2013) found a high expression of LCE gene in skin samples when kept at room temperature (21°C ± 2). Another study by Lv et al (2014) found varied RNA expression and degradation behaviors and suggested that environmental factors could play a role in gene expression. Nevertheless, our study provided evidence that minimal change in temperature did not disturb LCE1D gene expression.…”
Section: Discussionmentioning
confidence: 99%